Populist Challenges to Constitutional Interpretation in Europe and Beyond - Gárdos-Orosz, Fruzsina; Szente, Zoltán (Comparative Constitutional Change, 2021)
"This book explores the relationship between populism or populist regimes and constitutional interpretation used in those regimes. The volume discusses the question of whether contemporary populist governments and movements have developed, or encouraged new and specific constitutional theories, doctrines and methods of interpretation, or whether their constitutional and other high courts continue to use the old, traditional interpretative tools in constitutional adjudication. The book is divided into four parts. Part I contains three chapters elaborating the theoretical basis for the discussion. Part II examines the topic from a comparative perspective, representing those European countries where populism is most prevalent, including Austria, Croatia, the Czech Republic, Greece, Hungary, Italy, Poland, Romania, Spain, and the United Kingdom. Part III extends the focus to the United States, reflecting how American jurisprudence and academia have produced the most important contributions to the theory of constitutional interpretation, and how recent political developments in that country might challenge the traditional understanding of judicial review. This section also includes a general overview on Latin America, where there are also some populist governments and strong populist movements. Finally, the editors' closing study analyses the outcomes of the comparative research, summarizing the conclusions of the book. Written by renowned national constitutional scholars, the book will be essential reading for students, academics and researchers working in Constitutional Law and Politics."